UMP receives RM157,800 from UMW Toyota Motor - UMP, PNC (2020)
Universiti Malaysia Pahang (UMP) received RM157,800 from UMW Toyota Motor through UMP Foundation for the Ninja Project@UMP STEM Lab that will commence this April, involving more than 1,000 school students nationwide.